2017
DOI: 10.1080/03007995.2017.1335638
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, non-inferiority trial evaluating the efficacy and safety of omarigliptin, a once-weekly DPP-4 inhibitor, or glimepiride in patients with type 2 diabetes inadequately controlled on metformin monotherapy

Abstract: After 54 weeks, as add-on therapy to metformin, once-weekly omarigliptin was generally well tolerated and non-inferior to glimepiride in improving glycemic control, with a lower incidence of hypoglycemia and with weight loss vs weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…1 . Of 128 records identified by initial electronic search, 11 studies [ 14 16 , 20 27 ] met our inclusion criteria for the final narrative synthesis with a combined population of 8276 persons with T2DM. No additional study was identified by manual search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 . Of 128 records identified by initial electronic search, 11 studies [ 14 16 , 20 27 ] met our inclusion criteria for the final narrative synthesis with a combined population of 8276 persons with T2DM. No additional study was identified by manual search.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 trial [ 14 ] mostly involved patients with renal impairment (estimated glomerular filtration rate <60 mL/min per 1.73 m 2 ). Among 11 trials, 9 trials [ 14 , 15 , 20 24 , 26 , 27 ] compared the efficacy and safety of omarigliptin with placebo, 3 trials [ 16 , 20 , 25 ] compared the efficacy and safety of omarigliptin with other AHAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thank Doctors Takahara et al for their Letter to the Editor in response to our recently published paper in this journal entitled "A randomized, double-blind, non-inferiority trial evaluating the efficacy and safety of omarigliptin, a once-weekly DPP-4 inhibitor, or glimepiride in patients with type 2 diabetes inadequately controlled on metformin monotherapy" 1 . The phase 3 clinical program for omarigliptin demonstrated that it has a safety and efficacy profile similar to that of once-daily DPP-4 inhibitors, but because all subjects received both a once-weekly and a once-daily study drug to maintain blinding, these studies could not assess differences in patient satisfaction between a once-weekly and a oncedaily drug.…”
Section: Letter To the Editormentioning
confidence: 99%